Your freedom, your power : a kid's guide to the First Amendment - Matulli, Allison; Castro-Malaspina, Clelia (RP Kids, 2023)
Provides a guide for middle grade students on the First Amendment to the U.S. Constitution that begins with a history of the famous document, the Bill of Rights, and the federal court system. Breaks down the parts of the amendment into individual chapters and explains the way young people have used the First Amendment to organize and fight for change. Includes sidebars, charts, biographical profiles, and resources.